2017
DOI: 10.5424/sjar/2017152-9561
|View full text |Cite
|
Sign up to set email alerts
|

Is the increase of scale in the tropics a pathway to smallholders? Dimension and ecological zone effect on the mixed crop-livestock farms

Abstract: Mixed crop-livestock farms are widely spread in different tropical regions in the world; they contribute to food security, rural development, sustainability and poverty alleviation. The effect of scale on performance of dual purpose (DP) cattle farms was evaluated in two Mexican ecological zones: dry (DT) and wet tropics (WT). In 2011, a questionnaire of 184 items distributed into technical and social characteristics was applied to a representative sample of 3,285 farms with 50 or less cows (0.97%). The farms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
(47 reference statements)
1
18
0
4
Order By: Relevance
“…They indicate that producers should increase dimension at a great extent, otherwise a significant number of smallholders will be expelled from the system and will have to become laborers in their community or migrate to urban areas to find employment [32]. The increase of scale and intensification is an important aspect, although it is not enough for reaching a sustainable development in the tropics [2,7,10,11,17]. Our results showed that size was not associated to technological level.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…They indicate that producers should increase dimension at a great extent, otherwise a significant number of smallholders will be expelled from the system and will have to become laborers in their community or migrate to urban areas to find employment [32]. The increase of scale and intensification is an important aspect, although it is not enough for reaching a sustainable development in the tropics [2,7,10,11,17]. Our results showed that size was not associated to technological level.…”
Section: Discussionmentioning
confidence: 59%
“…The technological areas of genetics, reproduction, and animal health were the most implemented. The management and feeding areas need to be supported in order to develop adequate technologies for wet zones as record systems, grazing planting, crop residues, and adopting the mechanical milking [2,7,8,13,16,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Este nivel de adopción es bajo, y concuerda con estudios realizados en sistemas de producción de bovinos de doble propósito en México, que han identificado que solo entre el 1 % (Vilaboa & Díaz, 2009) y 6 % (Chalate et al, 2010) de los productores llevan a cabo la práctica de ensilaje. Un estudio reciente que analiza información de 2.187 unidades de producción en el trópico seco de México identificó que solo el 17,7 % de las unidades de producción realizan la práctica de ensilaje; este mismo estudio analiza la información por tamaño del rancho, e identifica que el mayor porcentaje de adopción (21,9 %) se encuentra con productores de tamaño medio, que tienen entre 20 y 50 vacas reproductoras (Rangel et al, 2017b).…”
Section: Ecuaciónunclassified